2011
DOI: 10.1016/j.jcs.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

QTLs for malting flavour component associated with pre-harvest sprouting susceptibility in barley (Hordeum vulgare L.)

Abstract: chromosome 2H explained 6% of genetic variation but was significant in both years. 43The Australian variety Stirling contributed to higher LOX content for the three QTLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…As LOX content has not been a selection criterion in breeding programs to date, we speculate that low LOX is associated with other preferred malting quality traits. This phenomenon has also been observed in QTL mapping for many traits including enzyme activity for alpha-amylase and beta-glucanase [ 18 ]. A recently study demonstrated 9-lipoxygenase as modulator of local and systemic defense in Arabidopsis.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…As LOX content has not been a selection criterion in breeding programs to date, we speculate that low LOX is associated with other preferred malting quality traits. This phenomenon has also been observed in QTL mapping for many traits including enzyme activity for alpha-amylase and beta-glucanase [ 18 ]. A recently study demonstrated 9-lipoxygenase as modulator of local and systemic defense in Arabidopsis.…”
Section: Discussionmentioning
confidence: 68%
“…More recently, Jin et al . [ 18 ] found another 3 QTLs controlling LOX content in the Stirling/Harrington DH population. One QTL at chromosome 5HL contributed to 39 of genetic variation in LOX content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative trait loci (QTL) controlling malting quality and dormancy, which confers resistance to pre-harvest sprouting, are tightly linked (Ullrich et al, 2009;Castro et al, 2010;Jin et al, 2011). This association has complicated the development of malting barley cultivars resistant to pre-harvest sprouting and breeding for high levels of a-amylase may have inadvertently reduced resistance to pre-harvest sprouting (Lin et al, 2009;Edney et al, 2013).…”
Section: Core Ideasmentioning
confidence: 99%
“…Given the tight association between major malt quality and dormancy QTL, identification of cultivars which combine malt quality suitable for North American adjunct style brewing and resistance to pre-harvest sprouting has been a challenge for barley breeders (Ullrich et al, 2009;Castro et al, 2010;Jin et al, 2011;Edney et al, 2013). Malting cultivars developed in the United Kingdom commonly have a moderate degree of dormancy suggesting that combining resistance to pre-harvest sprouting with quality suitable for all-malt styles of brewing is an avenue that could be pursued by North American barley breeders selecting for high rainfall regions.…”
Section: Falling Number and Germinationmentioning
confidence: 99%